Implementation of Digital Marketing in Building Padang City Branding - Fitri Adona; Yusnani Yusnani; Sri Nita (PT Mattawang Mediatama Solution, 2023)
Competition between tourism marketers and tourists occurs on social media. As the Internet advances, travelers have begun to take on the role of content producers and have started uploading photos, videos, and travel comments – on Facebook, Instagram, Twitter, and YouTube –, and even making recommendations of sites or places visited and services received. 1) the purpose of the research (The purpose of this study is to examine how digital marketing is used as a promotional tool for city branding. City branding managers need to recognize the social working method of social media which is characterized as a storytelling space and requires active story makers). 3) the results (The findings show that city area managers are required to master the internet and digital marketing, including storytelling techniques to promote their city branding). 4) major findings (The status and social network of a storyteller also play a key role in city branding marketing). 2) data, materials, and methodology (This study focuses on the city of Padang but can also be applied to other cities).